Rupture of-prepubic tendon and ventral abdominal wall in a pregnant - BRAR, P S; SINGH, H; PRABHAKAR, S (The Indian Journal of Animal Reproduction, 2007)
A case of the prepubic tendon rupture, with complete ventral abdominal wall tearing with spontaneous separation of the gravid uterus fonn the cervix in a pregnant mare is reported.